Cleanliness is everybody's duty - Mohamad Radhi, Nor Ain (2012)
RESIDENTS' cooperation is needed to ensure that Clean Zone areas are kept clean. Selangor Local Authorities Clean Zone evaluation panel head Prof Dr Mohd Fuad Mohd Salleh said after an area had been announced as a Clean Zone, residents have to work with their local council to maintain cleanliness.